Association of aortic valvular complex calcification burden with procedural and long-term clinical outcomes after transcatheter aortic valve replacement . (7th September 2021) - Ko, Euihong; Kang, Do-Yoon; Ahn, Jung-Min; Kim, Tae Oh; Kim, Ju Hyeon; Lee, Junghoon; Lee, Seung-Ah; Kim, Dae-Hee; Kim, Ho Jin; Kim, Joon Bum; Choo, Suk Jung; Park, Seung-Jung; et al.
Abstract: Aims: This study aimed to assess the impact of valvular/subvalvular calcium burden on procedural and long-term outcomes in patients undergoing transcatheter aortic valve replacement (TAVR) for severe aortic stenosis (AS). Methods and results: In this prospective observational cohort study, we included patients with AS undergoing TAVR between March 2010 and December 2019. Calcium burden at baseline was quantified using multidetector computed tomography and the patients were classified into tertile groups according to the amount of calcium. Procedural outcomes [paravalvular leakage (PVL) or permanent pacemaker insertion (PPI)] and 12-month clinical outcomes (composite of death, stroke, or rehospitalization, and all-cause mortality) were assessed. A total of 676 patients (age, 79.8 ± 5.4 years) were analysed. The 30-day rates of moderate or severe PVL ( P -for-trend = 0.03) and PPI ( P -for-trend = 0.002) proportionally increased with the tertile levels of calcium volume. The 12-month rate of primary composite outcomes was 34.2% in low-tertile, 23.9% in middle-tertile, and 25.8% in high-tertile groups (log-rank P = 0.02). After multivariable adjustment, the risk for primary composite outcomes at 12 months was not significantly different between the tertile groups of calcium volume [reference = low-tertile; middle-tertile, hazard ratio (HR) 0.81; 95% confidence interval (CI) 0.54–1.22; P = 0.31; high-tertile, HR 0.93; 95% CI 0.56–1.57; P = 0.80]. A similar pattern was observed for all-cause mortality. Conclusion: The rates of PVL and PPI proportionally increased according to the levels of valvular/subvalvular calcium volume, while the adjusted risks for composite outcomes and mortality at 12 months were not significantly different. Graphical Abstract: